Does mandatory CSR reporting contribute to the reduction of income inequality in society? Exploring the mediating role of channel variables - Ashfaq Habib; Zafar Azam; Muhammad Asif Khan; Natanya Meyer (Journal of Applied Economics, 2025)
This study analyses the impact of mandatory Corporate Social Responsibility reporting on the Gini coefficient of Central European countries: a measure of income inequality in society (SDG-10), where CSR reporting is mandatory for a subset of listed firms. The ordered logit regression model indicates that mandatory CSR reporting significantly helps mitigate income inequality in society. Additionally, it is revealed that CSR reporting affects the Gini coefficient through green finance and green innovation, while other variables, such as financial constraints, financial reporting quality, and sustainable beta, are identified as partial channel mediators. The findings highlight the need for companies to strategically address CSR initiatives as an overarching business strategy to respond to stakeholder theory. Overall, the research provides important contributions to practitioners seeking increased social and organizational outcomes which will help stakeholder needs and add great value to the body of literature concerning CSR reporting and the income inequality paradox.